SOCIOLOGUL ANTON GOLOPENȚIA DESPRE PROBLEMELE TINERETULUI - RAȚĂ, Valeriu (BIBLIOPOLIS, 2020)
This article is a review of the volume Youth Guidance by the Romanian sociologist Anton Golopentia (1909-1951). The Guidance is an unfinished work conceived in his youth when he was studying in Berlin, Germany. The manuscript is in the form of fragments written on scattered sheets, finding in the archives of the family Golopentia, including also pages typed on a typewriter, corrections and additions grouped by dr. Sanda Golopenеtia, linguist, professor emeritus at Brown University in Providence, USA, daughter of the illustrious scholar. This paper certainly is not the definitive one that aspired A. Golopenţia, but allows the understanding of topics and problems.